MASTER CLASS AS A FORM OF INCREASING THE COMPETENCE OF TEACHERS IN THE CONDITIONS OF AN EDUCATIONAL CLUSTER - Ernazarova Gulnora Oblakulovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article reveals the approaches to the organization of innovative activities in educational organizations, to organize master classes for teachers in educational organizations in the conditions of an educational cluster. The content, modern approaches, innovative conditions for conducting master classes aimed at improving the system of professional development of teaching staff in an educational cluster by priority groups of competencies are considered.